(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Hydroxyurea is an approved therapy in the management of children suffering from sickle cell disease (SCD). In adults co-administration of hydroxyurea and L-Arginine in adult sufferers of SCD had shown some benefits. This study examined the effect of co-administration of hydroxyurea (15-35mg/kg/day) and L-Arginine (500 mg/day) for 6 weeks on blood pressure, haematological parameters, liver and antioxidant enzymes levels. The levels of these parameters when the subjects were on hydroxyurea alone were taken as control values. Results showed that the combined therapy (HU + L-Arginine) decreased SBP, DBP, MAP and PP (p <0.01 in each case) but increased %HbF, Hb and PCV (p< o.001 in each case). It elevated CAT, SOD, GPX (p < 0.001 in each case) but depressed MDA, AST, ALT and ALP (p < 0.001 in each case). The study shows that L-Arginine used as an adjunct to hydroxyurea therapy may be beneficial to children suffering from sickle cell anaemia